Sagittal plane kinematics during the transition run in triathletes - Rendos, N. K.; Harrison, B. C.; Dicharry, J. M.; Sauer, L. D.; Hart, J. M. (Journal of Science and Medicine in Sport, 2013)
Objectives Epidemiological evidence indicates more than 70% of all injuries that occur while training for or competing in triathlon happen during running. Maintaining an aerodynamic position on a bicycle during a triathlon places triathletes in a prolonged trunk flexed position which may affect lower extremity running biomechanics following cycling and influence both injury risk and performance in these athletes. The aim of this study was to compare sagittal plane running kinematics after a 30-min cycling protocol to a baseline run without prior exercise. Design Descriptive laboratory study. Methods Healthy participants with prior triathlon experience (n = 28; height = 1.73 ± 0.09 m; mass = 63.0 ± 7.7 kg; age = 24.6 ± 5.8 years) ran at a self-selected speed on a custom-built treadmill surrounded by a 12-camera motion analysis system before and after a 30-min cycling protocol (RPE 12-14). Three-dimensional kinematics were measured before, and at 2-min, 6-min, 10-min, and 14-min post-cycling. A 1 × 5 series of repeated measures univariate ANOVAs were used to determine changes in kinematic parameters resulting from the cycling protocol. Statistical significance was set a priori at (p < 0.05). Results Peak angles for anterior pelvic tilt (p < 0.001), hip flexion (p < 0.001), and spine extension (p < 0.001) increased and hip extension decreased (p < 0.001) at all time points while running following cycling compared to baseline. Conclusions Cycling in an aerodynamic position for 30 min induces changes in sagittal plane running kinematics of the spine, pelvis, and hip for at least 14 min following cycling. Alterations in kinematics may increase the risk for lower extremity injuries and affect running performance in triathletes.